STUDENTS’ RESPONSE THROUGH SELF-MONITORING ATTENTION TECHNIQUE IN WRITING SKIL - TARIGAN, KARISMA E.; SIBURIAN, ITA LESTARI (Jurnal Ilmiah Aquinas, 2020)
In writing process the students have to compose their writing by using their own choice of sentence structure and organize their own ideas in such a way that the reader can understand them. The aim of this study is to describe the students’ response after having been taught by using self-monitoring attention technique. The data in this study is use descriptive data. The results of this study were 57.10% students strongly agree, 35.05% students agree, 6.35% students quite agree, 0.30% students disagree, and 1.30% students strongly disagree. Most of the students were more active and enthusiastic during the process of teaching and learning through self-monitoring attention technique